(untitled) (Research, Society and Development, 2022)
Early childhood is a fundamental period of human development, the most favorable phase for gains in skills and functions of neuropsychomotor domains. Parents are essential in promoting an environment conducive to the development of their children. Health education actions are a strategy to face the adversities of child development. Objective: to map educational practices developed/used as a strategy for parents to stimulate child development at home. Method: Joanna Briggs Institute scoping review protocol. Eligibility criteria: data via CAPES portal, Latin American and Caribbean Literature (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) via the digital platform of the Virtual Health Library (VHL) and the Scientific Electronic Library Online (SciELO), PubMed and PEDro. Search in grey literature: Google Academic, Ministry of Health and World Health Organization (WHO). Search and selection results: final report presented in flowchart format according to prisma-scr model. Productions that report educational practices for child development (concept), at home (context) with parents (population) will be included. DECS/MESH descriptors and Boolean operators will be used for the search equation. Reference managers: Rayyan and Endnote. Two reviewers will screen, read and extract the information. The data will be classified and categorized thematically, based on bardin’s content analysis.